Assessing the Variance in Pupil Attainment: How Important is the School Attended?. (February 2018) - Wilkinson, David; Bryson, Alex; Stokes, Lucy
We explore the variation in pupil attainment at the end of secondary schooling in England. The paper links data on all schools and all pupils within these schools to analyse the role of the school in accounting for this variation. We analyse a number of different indicators of pupil attainment including value added between the end of primary and secondary schooling and attainment levels at the end of secondary schooling. We examine indicators that were the focus of the school accounting framework as well as other indicators that were not directly part of how schools were assessed. We show that schools account for a minority of the variance in pupil attainment, and the extent of the variation accounted for by the school is sensitive to the measure of pupil attainment used. In addition, we find that the majority of the explained school-level variance in attainment is related to school composition. However, most of the variance in attainment remains unexplained, raising questions about what other factors contribute to the variation in school performance.